2014
DOI: 10.1097/pas.0000000000000094
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α Expression in Tumor Cells as a Novel Prognostic Marker for Diffuse Large B-cell Lymphoma, Not Otherwise Specified

Abstract: Several cytokines promote malignant cell growth and are therefore believed to contribute to disease aggressiveness. The cytokine tumor necrosis factor-α (TNF-α) acts as a tumor-promoting factor and has been linked to all tumorigenic stages in many cancers. Here, we evaluated 62 lymphoma tissue specimens from patients having diffuse large B-cell lymphoma, not otherwise specified (DLBCL, NOS) by immunostaining with anti-TNF-α antibody. Cytoplasmic TNF-α reactivity in ≥20% of the tumor cells was considered positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…A marked increase in B-cell activation is commonly seen in HIV infection, which is driven by the overproduction of B-cell stimulatory cytokines, such as IL-6 and IL-10, as well as by stimulation of B-cells by HIV and other microbial antigens 94. In addition, HIV itself induces the production of inflammatory cytokines that cause B-cell stimulation, proliferation, and activation, and the cell lines derived from HIV-NHL have been found to express cytokines including interleukin 6, 10, and tumor necrosis factor-α 95–98. B-cell activation is characterized by lymphocyte proliferation, class switch recombination (CSR), and somatic hypermutation, all of which are prone to resultant errors in DNA that may lead to lymphomagenesis.…”
Section: Biomarkers Used In Hiv-nhl Diagnosis/prognosismentioning
confidence: 99%
“…A marked increase in B-cell activation is commonly seen in HIV infection, which is driven by the overproduction of B-cell stimulatory cytokines, such as IL-6 and IL-10, as well as by stimulation of B-cells by HIV and other microbial antigens 94. In addition, HIV itself induces the production of inflammatory cytokines that cause B-cell stimulation, proliferation, and activation, and the cell lines derived from HIV-NHL have been found to express cytokines including interleukin 6, 10, and tumor necrosis factor-α 95–98. B-cell activation is characterized by lymphocyte proliferation, class switch recombination (CSR), and somatic hypermutation, all of which are prone to resultant errors in DNA that may lead to lymphomagenesis.…”
Section: Biomarkers Used In Hiv-nhl Diagnosis/prognosismentioning
confidence: 99%
“…There have been some reports showing a relationship between biological markers on the tumor cells (eg, bcl2, CD44, and tumor necrosis factor-a expression), as well as the Ki67 labeling index and patients' prognosis. 4,5 In particular, an immunophenotypic analysis revealed that the germinal center B-cell-like (GCB) phenotype has a better prognosis than non-germinal center B-cell-like (non-GCB) phenotype, which is an independent predictor of IPI. 6 The tumor microenvironment is important for the development and progression of tumors, and influences the patients' prognosis 7 ; thus, it is essential for the development of novel treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of individual markers may be associated with prognosis in DLBCL and related lymphomas, supporting the idea that this is a complex and heterogeneous group of neoplasms, and each year additional markers are put forward for evaluation [5][6][7][8][9][10][11][12][13][14][15][16][17][18] (Table 5). While a plethora of unique aspects of DLBCL is prognostic, only those markers that have been vetted by extensive clinical study and can be routinely applied are the primary focus of this report.…”
Section: Diagnosis Prognosis and Therapymentioning
confidence: 99%